The erosion of union membership in Germany: determinants, densities, decompositions - Bernd Fitzenberger; Karsten Kohn; Qingwei Wang (Institute for the Study of Labor (IZA), 2006)
Union density in Germany has declined remarkably during the last two decades. We estimate socio-economic and workplace-related determinants of union membership in East and West Germany using data from the German Socio-Economic Panel by means of Chamberlain-Mundlack correlated random effects probit models. Drawing on the estimates, we project net union densities (NUD) and analyze the differences between East and West Germany as well as the corresponding changes in NUD over time. Blinder-Oaxaca decompositions show that changes in the composition of the work force have only played a minor role for the deunionization trends in East and West Germany. In East-West comparison, differences in the characteristics of the work force reflect a lower quality of membership matches in East Germany right after German unification.
Keywords: J51; 330; union membership; union density; correlated random effects probit model; decomposition analysis; East Germany; West Germany